Cycloartane triterpenoids from Actaea vaginata with anti-inflammatory effects in LPS-stimulated RAW264.7 macrophages. (April 2019) - Fang, Zhu-Jun; Zhang, Tian; Chen, Shi-Xin; Wang, Yan-Lan; Zhou, Chang-Xin; Mo, Jian-Xia; Wu, Yong-Jiang; Xu, You-Kai; Lin, Li-Gen; Gan, Li-She
Abstract: Five undescribed cycloartane triterpenoids, including two cycloartane trinor-triterpenoids, were isolated from a 70% ethanol extract of the whole plant of Actaea vaginata (Ranunculaceae), together with thirteen known cycloartane triterpenoids. Their structures were determined by spectroscopic techniques and quantum chemical calculations for intramolecular noncovalent interactions with reduced density gradient method. All compounds were evaluated for their anti-inflammatory effects by a lipopolysaccharide (LPS)-stimulated nitric oxide (NO) production model in RAW264.7 macrophage cells, and some showed potent inhibitory effects with IC50 values ranging from 5.0 to 24.4  μ M. Further mechanism studies showed that one compound dose-dependently suppressed LPS-induced NO production and pro-inflammatory cytokines secretion, and decreased the expression of iNOS, through inhibiting NF- κ B activation. Graphical abstract: Five undescribed cycloartane triterpenoids were identified from Actaea vaginata . Compound3 suppressed NO production and the expression of pro-inflammatory cytokines and iNOS in RAW264.7 cells.Image 1 Highlights: Five undescribed cycloartane triterpenoids were identified from Actaea vaginata. Two compounds represent the first examples of cycloartane trinor-triterpenoids. A reduced density gradient calculation was applied to determine the configuration. Anti-inflammatory activity through inhibiting NF-κB activity were discussed.